Management OF SSB Football School In Ujumbou Village, Sirenja District, Donggala Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to describe the implementation of management functions that include planning, organizing, leadership, and control at the Ujumbou Football School (SSB), located in Ujumbou Village, Sirenja District, Donggala Regency. This study uses a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. The informants in this study consisted of coaches and assistant coaches. The results of the study indicate that the management function at SSB Ujumbou has been implemented quite well. In terms of planning, SSB has clear objectives and written training programs that are arranged weekly and adjusted to the events or competitions being participated in. In terms of organization, there is an effective division of tasks between coaches and administrators, as well as active involvement of parents through routine communication and logistical support. The leadership function is carried out with a communicative and motivational approach, with efforts to build discipline and enthusiasm for student training. Meanwhile, control is carried out through evaluation of training results, supervision of equipment, and handling of obstacles collectively. Thus, the management of SSB Ujumbou demonstrates participatory and adaptive management practices, although it still requires strengthening in terms of strategic planning and sustainable support for infrastructure facilities.